The effect of LMX and age dyadic differences on the satisfaction with the feedback and the leader - Costa, Joana Isabel Duarte Cardoso Matança da (2019)
There are a lot of companies and employees dissatisfied with the existing performance appraisal systems. It is well known and studied in the literature that performance feedback has a huge impact on learning and achievement of the employees, so it turns out to be very important to understand this process and all the variables that may influence it. It is studied that the social context in which the feedback process is embedded may influence employees’ reactions to the feedback. Leader-Member Exchange and age dyadic differences are some of the variables that have been studied in the leadership literature. This study now addresses how the connection between Leader-Member Exchange and age dyadic differences is related with the satisfaction with the feedback and the leader, especially in a poor feedback scenario. To understand this connection, we studied the role of attributions as a mediator of this process. The data collected for this study was obtained from a sample of 103 employees from Portuguese companies with performance appraisal systems. In general, results revealed that Leader-Member Exchange has an impact in the satisfaction with the feedback and with the leader, External and Unstable Attributions mediate the relationship between Leader-Member Exchange and the satisfaction with the leader only when the employee is older than the leader and age differences moderate the mediation of the relationship between Leader-Member Exchange and external and unstable attributions. The implications of these findings for both theory and practice are discussed in this study.